Analysis of welding zinc coated steel sheets in zero gap configuration by 3D simulations and high speed imaging - Koch, Holger Michael; Kägeler, Christian; Otto, Andreas; Schmidt, Michael (Physics Procedia, 2011)

Laser based joining of monocrystalline silicon foils - Schaefer, Lorenz; Tangermann-Gerk, Katja; Koch, Holger Michael; Hessmann, Maik; Kunz, Thomas; Frick, Thomas; Schmidt, Michael (Physics Procedia, 2010)
Monocrystalline silicon is the basic material for many electronic applications such as solar cells or detectors. Joining of silicon foils is a very difficult task due to the brittleness of the monocrystalline silicon. It was shown that it is possible to join silicon substrates with thicknesses in the millimetre range by laser beam welding [1, 2, 3]. To qualify the laser based joining under industrial environment a stable process has to be ensured. In this paper an analysis of the laser based joining process of silicon foils with a thickness of 50 μm is presented. The welding process is analyzed by finite element simulation and experimental studies. The simulation shows that at the end of the welding process a strong deformation of the foils appears. To validate the simulation model experimental investigations were carried out. The simulation and experimental results correspond very well in regard of the time dependent behaviour of the deformation. The deformation behaviour is attributed to the buckling mechanism.
Created from Fastlane, Scopus look-up
Keywords: Laser beam welding; Silicon foils; Simulation

Laser Deep Penetration Welding Simulation Based on a Wavelength Dependent Absorption Model - Koch, Holger Michael; Leitz, Karl-Heinz; Otto, Andreas; Schmidt, Michael (Physics Procedia, 2010)

Numerical Simulation of Drilling with Pulsed Beams - Leitz, Karl-Heinz; Koch, Holger Michael; Otto, Andreas; Maaz, Alexander; Löwer, Thorsten; Schmidt, Michael (Physics Procedia, 2012)

Numerical simulation of process dynamics during laser beam drilling with short pulses - Leitz, Karl-Heinz; Koch, Holger Michael; Otto, Andreas; Schmidt, Michael (Applied Physics A-Materials Science & Processing, 2012)

Numerical Simulations - A Versatile Approach for Better Understanding Dynamics in Laser Material Processing - Otto, Andreas; Koch, Holger Michael; Leitz, Karl-Heinz; Schmidt, Michael (Physics Procedia, 2011)

Three Dimensional Simulation of Laser Beam Welding - Koch, Holger Michael; Leitz, Karl-Heinz; Otto, Andreas (Proceedings of the LANE 2007, 2007)
LFT Import::2019-08-05 (1444)